DETERMINASI BUDAYA TRI HITA KARANA DAN PENGETAHUAN AKUNTANSI TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH DI KOTA DENPASAR - Harthawan, I Gusti Ngurah Putra; Sudira, I Gd Ari; Arnata, I Komang (KRISNA: Kumpulan Riset Akuntansi, 2025)
Micro, small and medium enterprises have an important role in increasing economic growth in a region. Micro, small and medium enterprises are one of the potential tax contributors. Research on micro, small and medium enterprises is very necessary to spur the growth of this business group so that the regional economy continues to move positively. This study aims to determine the influence of Tri Hita Karana (THK) culture and accounting knowledge on the performance of micro, small and medium enterprises in Denpasar City. The number of respondents involved in the study was 100 micro, small and medium enterprise managers. The results of the regression test showed that if the THK culture improves, the performance of micro, small and medium enterprises will increase. The results of the study also showed that accounting knowledge significantly drives the increase in the performance of micro, small and medium enterprises.